2023
DOI: 10.3389/fpsyg.2023.1154442
|View full text |Cite
|
Sign up to set email alerts
|

ERP evidence for emotion-specific congruency effects between sentences and new words with disgust and sadness connotations

Abstract: Introduction:The present study investigated how new words with acquired connotations of disgust and sadness, both negatively valenced but distinctive emotions, modulate the brain dynamics in the context of emotional sentences.Methods:Participants completed a learning session in which pseudowords were repeatedly paired with faces expressing disgust and sadness. An event-related potential (ERP) session followed the next day, in which participants received the learned pseudowords (herein, new words) combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…It was found that faces were more effective for acquiring disgusting connotations and comparable to sentences for sad connotations. The research was followed by two ERP studies that explored the brain spatiotemporal dynamics when processing such emotional pseudowords whose connotations were acquired using faces in both a lexical-semantic decision task (Gu et al, 2022) and a sentence emotional congruency judgment task (Gu et al, 2023). Distinctive ERP patterns were spotted for the two sets of L1 emotional pseudowords and thus further proved that the acquisition was effective and successful.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that faces were more effective for acquiring disgusting connotations and comparable to sentences for sad connotations. The research was followed by two ERP studies that explored the brain spatiotemporal dynamics when processing such emotional pseudowords whose connotations were acquired using faces in both a lexical-semantic decision task (Gu et al, 2022) and a sentence emotional congruency judgment task (Gu et al, 2023). Distinctive ERP patterns were spotted for the two sets of L1 emotional pseudowords and thus further proved that the acquisition was effective and successful.…”
Section: Introductionmentioning
confidence: 99%